O santuário de São Severino do Ramos : expressão de religiosidade no nordeste brasileiro - Rocha, Crévio Adelino da (2013)
The research aimed to analyze the relationship between the devotee and the holy Shrine of St. Severino Ramos in Paudalho-PE, seeking to identify the symbolic exchanges in manifestations of popular devotions. The foundation was built from the works of Pierre Bourdieu, Alberto Beckhauser, João de Deus Gois, Eduardo Hoornaert, Faustino Menezes and Renata Teixeira, Sylvana Brandão, among others. From the methodological point of view, it is considered that the path followed was a phenomenological approach using specialized bibliography of popular religiosity in studies to understand the concepts related to the topic, between devotion to the saints, shrines, religion and popular religion, Catholicism and sanctoral religious tourism. A descriptive exploratory survey was used to investigate the relationship of symbolic exchanges on promises, miracles and votive among devotees of San Severino Ramos, at the Shrine of St. Severino Ramos in Paudalho-PE, in the light of the notion that all search for the sacred has as starting point urgent human needs, as well as gratitude for such needs have been met. The work consists of three chapters with the first contextualizes them on devotion to the saints throughout history, addressing questions about the origin; devotion to the saints in Brazil; devotion to St. Severino Ramos and sanctuary that bears his name in Paudalho-PE. The second chapter covers the concepts related to the theme of religion and interfaces with the popular religion, popular religion and Catholicism sanctoral; popular religiosity and religious tourism. The third focuses on the religious manifestations and symbolic exchanges at the Shrine of St. Severino Ramos bringing the search results. From the analysis, we sought to understand the religious phenomenon that occurs in that area to subsequently submit final comments and proposals on the issue to thereby contribute to the study of the religiosity of the northeastern people and therefore collaborate to produce a knowledge of interdisciplinary nature of the field itself as epistemological Sciences of Religion.